Analysis on Spatial Disturbance Influence of Surrounding Rock Stress in the Staggered Roadways and Its Control Countermeasures. (15th June 2022) - Bu, Qingwei; Yuan, Benqing; Ye, Meng; Xu, Nuo
Abstract : Combined with specific engineering examples, the spatial disturbance influence characteristics and laws of the surrounding rock stress in the staggered roadways are analyzed by numerical simulation. This paper concludes that (1) compared with the surrounding rock pressure behavior of the general roadway, the surrounding rock stability of the staggered roadway is relatively poor, showing the characteristics of the local serious roadway rock pressure behavior, such as the intensified destruction of the roadway side, the failure and fracture penetration of the surrounding rock between the roadways, and the relatively serious deformation of the surrounding rock. The reason is that the stress of the surrounding rock at the staggered roadway position is obviously superimposed and disturbed by each other; (2) the influencing factors of the failure and instability of the surrounding rock between interlaced roadways are as follows: the greater the buried depth and the smaller the distance between roadways, the more intense the superposition disturbance of the surrounding rock stress between roadways; the smaller the horizontal azimuth, the greater the influence range of superposition disturbance of surrounding rock stress between roadways; the more unbalanced the original rock stress field, the worse the stability of the surrounding rock between roadways, resulting in the more serious failure and instability of the surrounding rock between roadways; (3) for the staggered roadway layout, increasing the distance between roadways, the closer to the orthogonal layout and selecting the arch section of the lower roadway is conducive to the bearing stability of the surrounding rock between roadways; (4) constrained by the space conditions of staggered roadway, the role of bolt and cable support is limited. Passive support is the key to realize the safety and stability of surrounding rock of staggered roadway, so the control technical scheme of active and passive combined support in staggered roadway position is put forward, the combined support of the upper roadway "bolt + cable + shotcrete + concrete cushion of floor" and lower roadway "bolt + cable + U-shaped steel support passive reinforcement + shotcrete" within the spatial disturbance influence the range of surrounding rock stress in the staggered roadways, and the technical scheme can achieve satisfactory supporting effect.